2012
DOI: 10.1007/s00167-012-2235-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic single-bundle ACL reconstruction with modified double-layer bone-patellar tendon-bone allograft

Abstract: Therapeutic, retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In comparison with previous BPTB preparation procedures such as a BPTB and gracilis tendon composite or DB BPTB graft [15, 29], the present modification of the BPTB graft was original. The BPTB allograft was modified into a column of mean 9.9 mm in diameter with wider cross‐sectional area than traditional BPTB of a rectangle with 10 mm in width and 4 mm in height [4]; significantly lesser anterior laxity and better knee function have been achieved than those of traditional BPTB ACL reconstruction [16]. After the modification, SB ACL reconstruction even achieved comparable clinical outcomes to DB reconstruction with tibialis anterior allograft in the present study.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In comparison with previous BPTB preparation procedures such as a BPTB and gracilis tendon composite or DB BPTB graft [15, 29], the present modification of the BPTB graft was original. The BPTB allograft was modified into a column of mean 9.9 mm in diameter with wider cross‐sectional area than traditional BPTB of a rectangle with 10 mm in width and 4 mm in height [4]; significantly lesser anterior laxity and better knee function have been achieved than those of traditional BPTB ACL reconstruction [16]. After the modification, SB ACL reconstruction even achieved comparable clinical outcomes to DB reconstruction with tibialis anterior allograft in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…Single‐bundle reconstruction with modified BPTB allograft has been described in a previous study [16]. The BPTB allograft was shaped into a column of 25 mm in length, 10 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doubling the cross‐sectional area of the monolayer BPTB resulted in better anterior stability compared with the single‐layer BPTB. Also, the DBPTB allograft eliminated “dead space” [10] and therefore the “windshield wiper” effect [18], factors that are thought to interfere with tendon‐to‐bone healing and that lead to post‐operative bone tunnel enlargement [11, 17, 18]. Consequently, the DBPTB patients achieved better clinical results than those receiving the traditional BPTB allograft.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2‐year retrospective clinical study, Kang et al [11] reported that the double‐layer bone‐patellar tendon‐bone (DBPTB) allograft significantly improved anterior stability and function of the knee. To the best of the authors’ knowledge, there have been no prospective studies of DBPTB grafts; therefore, the present study was designed to evaluate the clinical outcomes of DBPTB grafting for ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%